Investigating factors affecting employees’ work productivity - Izhar Izhar; Radiman Radiman; Sri Fitri Wahyuni (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — This study aims to determine the work productivity of employees, which includes work attitudes, skill levels, education, and leadership style, both partially and simultaneously influencing employees' work productivity.Method — This study employs a quantitative approach, utilizing multiple linear regression analysis techniques. The population comprised 34 respondents from the Medang Deras District office, with a saturated sample.Result — Based on the study's results, it was concluded that work attitude, skill level, and employee education had a partially positive effect on employee productivity, while leadership style had a partial negative effect on productivity. Additionally, the study found that work attitude, skill level, education, and leadership style had a positive simultaneous effect on work productivity.Contribution — The academic contribution of this research lies in its innovative approach by introducing additional variables and combining various disciplines such as Management, Psychology, and Education to explore the interplay between work attitude, leadership style, skill levels, and education, ultimately shedding light on their collective impact on employee productivity.